2007
DOI: 10.1167/iovs.06-0884
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Endostatin by Matrix Metalloproteinase and Cathepsin from Human Limbocorneal Epithelial Cells Cultivated on Amniotic Membrane

Abstract: MMP-7 and cathepsins B and V are involved in the generation of endostatin by HLE cells. Facilitating endostatin generation may be a novel physiological function of the cornea-specific cathepsin V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Rather, our studies uncovered the ability of SorCS2 to facilitate production and/or release of endostatin from this cell type. Endostatin is cleaved from its precursor collagen XVIII by various proteases, including cathepsins and metalloproteinases (Felbor et al, ; Ferreras, Felbor, Lenhard, Olsen, & Delaissé, ; Ma et al, ). To date, it is not clear which protease plays the major role in generating endostatin in vivo and whether processing takes place intracellularly or in the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, our studies uncovered the ability of SorCS2 to facilitate production and/or release of endostatin from this cell type. Endostatin is cleaved from its precursor collagen XVIII by various proteases, including cathepsins and metalloproteinases (Felbor et al, ; Ferreras, Felbor, Lenhard, Olsen, & Delaissé, ; Ma et al, ). To date, it is not clear which protease plays the major role in generating endostatin in vivo and whether processing takes place intracellularly or in the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of matrikines, such as angiostatin, arresten, canstatin, and tumstatin, exert anti-angiogenic functions by reducing endothelial cell proliferation. Cleavage of plasminogen by MMP2, MMP3, MMP7, MMP9, MMP12, and MMP19 generates angiostatin (Patterson and Sang 1997;Cornelius et al 1998;Lijnen et al 1998;Moses and O'Reilly 2003;Brauer et al 2011), and endostatin is generated through cleavage of collagen XVIII by MMP3, MMP9, and MMP13 (Ma et al 2007;Bendrik et al 2010;Fukuda et al 2011). Besides MMPs, different cathepsin family members, including the cysteine cathepsins L and S (Felbor et al 2000;Veillard et al 2011) and the aspartic cathepsin E (Shin et al 2007), have been shown to generate endostatin from collagen XVIII.…”
Section: Angiogenesismentioning
confidence: 99%
“…Collagen XVIII has been shown to be cleaved by several proteases, including MMP‐7, MMP‐14, and Cathepsin L, to generate endostatin‐containing fragments and endostatin [12–14]. MMP‐7 cleaves NC‐1 fragments of collagen XVIII to generate neostatin‐7, which contains an additional 60 amino acids at the N‐terminal of endostatin.…”
Section: Introductionmentioning
confidence: 99%